Treatment of paper mill wash water using combined ozonation and upflow anaerobic sludge blanket (UASB) process at different system configurations and hydraulic retention times - Lapada, Catherine M. (2012)
The efficiency of a treatment process for paper mill wastewater (PMW) using and upflow anaerobic sludge blanket (UASB) reactor at various hydraulic retention time (HRT) values integrated with ozonation as pre- or post-treatment was investigated. In each process sequence, the UASB reactor was continuously run at HRTs of 24, 18 and 12 h and ozonation was carried out at constant ozone dosage of 0.5 g O3/h-L. The total and dissolved COD, methane production, color, turbidity, total suspended solids (TSS), BOD, phenol and pH levels were measured during the operation. Among the process sequence applied, the best process based on the highest COD removal was that consisting of 10-minute ozonation pre-treatment followed by digestion in a UASB reactor at 24 h HRT. This process sequence has achieved 94.21% COD reduction and 77.25% color removal. The BOD/COD ratio increased from 0.16 to 0.39 after 10-min pre-ozonation and further increased to 0.67 after being treated at 24 h HRT in a UASB reactor. Phenol concentration decreased by 90%. Thus, ozonation as preliminary treatment at optimum reaction time to convert the initially persistent organic compounds into more biodegradable product is a promising treatment strategy for PMWW. Optimizing both the ozonation treatment and the biological process is a feasible strategy in reducing the cost while improving its performance.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Sewage -- Purification -- Anaerobic treatment; Ozonation